Estimation of salivary ferritin in children with childhood caries – a cross sectional study - Kotian, Niharika; Gurunathan, Deepa (Brazilian Dental Science, 2021)
Objective: Early childhood caries is the presence of dental caries in a child upto seventy one months of age. Saliva plays a major role in maintaining good oral health. The composition of saliva acts as a marker for oral health and the salivary proteins help in modulating the oral microflora in the oral cavity. Some salivary biomarkers help in detecting caries risk and can also predict their prognosis. Ferritin is one of the major biomarkers present in the saliva which acts as an iron binding protein and also as a monitoring tool in children suffering from iron deficiency. The ferritin levels are in increased in serum as well as in saliva to balance the deficiency of iron in the body. Material and methods: Sixty children were selected for the study aged between three to six years. The saliva sample was collected using standard spit method in a sterile container and Ferritin was tested in the samples by Chemiluminescence microparticle immunoassay(CMIA). Results: Salivary ferritin was found to be higher in the saliva of children with early childhood caries(mean value= 5.867) than in children without early childhood caries(mean value= 3.412). Conclusion: A direct association is present between salivary ferritin levels and dental caries. Increased level of ferritin is observed in children with Early childhood caries. Clinical relevance: The level of salivary ferritin is found to be raised in the present study in children with Early childhood caries. The exact mechanism is although not known it can be assumed that the children with early childhood caries might have deficiency of iron which has led to the increased amount of salivary ferritin in the saliva. KeywordsSalivary ferritin; Early childhood caries; Salivary proteins; Saliva; Iron deficiency